Effect of ozone treatment on microbiological and physicochemical properties of soymilk beverage. Issue 1 (February 2020) - Anam, C; Perwitasari, A A; Jannah, H N; Yaqin, N; Yulianto, E; Sasmita, E; Restiwijaya, M; Kinandana, A W; Aryanto, F; Nur, M
Abstract: Ozone is a strong oxidant and potent desinfecting agent. An ozonation process for microbial inactivation in some beverages has been done. Accordingly, the ozonation process was performed in soymilk. Soymilk was ozonated under different exposure time: 1, 3, 5, 10, and 15 minutes and evaluated for the changes of microbiological and physicochemical properties. The assays were carried out by using an experimental design fully randomized and results were statistically evaluated by Duncan's Multiple Range test (p < 0.05). Following the ozone treatment, a significant reduction in pH occurred at 1 minute treatment, whereas a significant increasement was recorded after 3 minutes treatment. A significant increasement in total dissolve solid was observed at 5, 10, and 15 minutes. Microbial reduction was recorded 0.19 log cycles at 1 min., 0.35 log cycles at 3 min, and 0.57 log cycles at 5 minutes ozone treatment. In contrast, an increase of microbial population occurred at 10 and 15 minutes. The findings presented here could be a prelude for the potential application of ozone treatment of soymilk in the food industry.